Correction: Novel two-dimensional tetrahexagonal boron nitride with a sizable band gap and a sign-tunable Poisson's ratio. Issue 25 (21st June 2021) - Kilic, Mehmet Emin; Lee, Kwang-Ryeol
Abstract : Correction for 'Novel two-dimensional tetrahexagonal boron nitride with a sizable band gap and a sign-tunable Poisson's ratio' by Mehmet Emin Kilic et al., Nanoscale, 2021, 13, 9303–9314, DOI: ; 10.1039/D1NR00734C .